2014
DOI: 10.14233/ajchem.2014.16255
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Partial Least Squares Modelling for Determination of Soil Nitrogen by Fourier Transform Near-Infrared Spectrometry

Abstract: The concentrations of nitrogen in soil were analyzed by the Fourier transform near-infrared (FT-NIR) spectrometry. Using partial least squares (PLS) regression, wavelength selection is a vital task for improving the modeling ability because the predictive results partially depend on the signal-to-noise ratio of the modeling wavelengths, The discrete single-and-favorite combination linear regression (DSFCLR) method was proposed for selecting the informative wavelength combination. And the discrete combination p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The prospective precise of calibration model will be difficult to improve if the full-range NIR spectrum is used. Wavelength selection is quite necessary for model optimization [11] [12]. Successive projection algorithm (SPA) is an effective method to search wavelengths (or wavelength combinations) which are most informative and with least colinearity [13].…”
Section: Introductionmentioning
confidence: 99%
“…The prospective precise of calibration model will be difficult to improve if the full-range NIR spectrum is used. Wavelength selection is quite necessary for model optimization [11] [12]. Successive projection algorithm (SPA) is an effective method to search wavelengths (or wavelength combinations) which are most informative and with least colinearity [13].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] It has been demonstrated that SOC can be measured in the eld with enhanced measurement stability at the expense of a slight decrease in accuracy compared to laboratory experiments. [18][19][20] Once the spectra have been calibrated for SOC, the chemometric methods can provide a rapid and inexpensive estimation of SOC in the eld.…”
Section: Introductionmentioning
confidence: 99%